ANALISIS LINGKUNGAN INTERNAL DAN EKSTERNAL Studi Kasus : PT. Intan Periwara - Aulia Maharani; Sutantri; Iva Khoiril Mala (LPPM Sekolah Tinggi Ilmu Ekonomi - Studi Ekonomi Modern, 2024)
PEST (Political, Economic, Social, and Technological Analysis), which examines aspects of Indonesia's macro environment (economic, technological, political, legal, and socio-cultural), is a component of external environmental analysis. The second external environment study is a competitive pressure model that outlines five circumstances: the bargaining power of suppliers, competition from current competitors, threats from new competitors, and threats from substitute goods or services. Context diagrams are used in internal environment analysis to illustrate how systems communicate with external parties involved in an organization's business. The relationship between the internal system and the external entity of the PT can be explained by a context diagram. This diagram visually illustrates the interaction between the system and four main external groups: printers, authors, representatives, and buyers. The buyer group is divided into two major segments, namely the general public and students from kindergarten to high school levels, which reflects the demographic diversity reached by PT in its operational activities.